The effect of specific bioactive collagen peptides on function and muscle remodeling during human resistance training. (13th December 2022) - Balshaw, Thomas G.; Funnell, Mark P.; McDermott, Emmet; Maden‐Wilkinson, Thomas M.; Abela, Sean; Quteishat, Btool; Edsey, Max; James, Lewis J.; Folland, Jonathan P.
Abstract: Aim: Bioactive collagen peptides (CP) have been suggested to augment the functional, structural (size and architecture), and contractile adaptations of skeletal muscle to resistance training (RT), but with limited evidence. This study aimed to determine if CP vs. placebo (PLA) supplementation enhanced the functional and underpinning structural, and contractile adaptations after 15 weeks of lower body RT. Methods: Young healthy males were randomized to consume either 15 g of CP ( n = 19) or PLA ( n = 20) once every day during a standardized program of progressive knee extensor, knee flexor, and hip extensor RT 3 times/wk. Measurements pre‐ and post‐RT included: knee extensor and flexor isometric strength; quadriceps, hamstrings, and gluteus maximus volume with MRI; evoked twitch contractions, 1RM lifting strength, and architecture (with ultrasound) of the quadriceps. Results: Percentage changes in maximum strength (isometric or 1RM) did not differ between‐groups (0.684 ≤ p ≤ 0.929). Increases in muscle volume were greater (quadriceps 15.2% vs. 10.3%; vastus medialis (VM) 15.6% vs. 9.7%; total muscle volume 15.7% vs. 11.4%; [all] p ≤ 0.032) or tended to be greater (hamstring 16.5% vs. 12.8%; gluteus maximus 16.6% vs. 12.9%; 0.089 ≤ p ≤ 0.091) for CP vs. PLA. There were also greater increases in twitch peak torque (22.3% vs. 12.3%; p = 0.038) and angle of pennation of the VM (16.8% vs. 5.8%, p = 0.046), but not other muscles, for CP vs. PLA. Conclusions: CP supplementation produced a cluster of consistent effects indicating greater skeletal muscle remodeling with RT compared to PLA. Notably, CP supplementation amplified the quadriceps and total muscle volume increases induced by RT.